2006
DOI: 10.1161/01.str.0000226624.93519.78
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of Familial Connective Tissue Alterations Associated With Cervical Artery Dissections Suggests Locus Heterogeneity

Abstract: Background and Purpose— Cervical artery dissections (CAD) can be associated with connective tissue aberrations in skin biopsies. The analysis of healthy relatives of patients suggested that the connective tissue phenotype is familial with an autosomal dominant inheritance. Methods— We performed genetic linkage studies in 3 families of patients with CAD. Connective tissue phenotypes for the patients and all family… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 33 publications
(29 reference statements)
1
28
1
Order By: Relevance
“…56 A third study performed a whole genome linkage analysis and identified 2 suggestive candidate loci on chromosomes 15q24 and 10q26 with logarithm of odds scores of 2.1 and 1.9 in one family. 49 The same regions were, however, excluded in 2 other families, suggesting locus heterogeneity of the connective tissue phenotype. 49 …”
Section: Linkage Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…56 A third study performed a whole genome linkage analysis and identified 2 suggestive candidate loci on chromosomes 15q24 and 10q26 with logarithm of odds scores of 2.1 and 1.9 in one family. 49 The same regions were, however, excluded in 2 other families, suggesting locus heterogeneity of the connective tissue phenotype. 49 …”
Section: Linkage Studiesmentioning
confidence: 99%
“…49 The same regions were, however, excluded in 2 other families, suggesting locus heterogeneity of the connective tissue phenotype. 49 …”
Section: Linkage Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…12 A candidate locus on chromosome 15q2 was recently found by genetic linkage analysis in 1 large family with connective tissue alterations associated with CAD. 13 That study of 3 families with sporadic CAD patients analyzed the segregation of the connective tissue phenotype as an intermediate marker. A segregation analysis of subjects affected with CAD was virtually impossible because familial cases of CAD were too rare.…”
mentioning
confidence: 99%
“…In some families the connective tissue abnormalities, but not sCAD as such, were present in multiple family members compatible with autosomal dominant inheritance [4]. In one of these families suggestive linkage between connective tissue abnormalities and genetic markers on chromosome 15q24 has recently been demonstrated [5]. The candidate region comprises the lysyl oxidase-like 1 ( LOXL1 ) gene which is an excellent functional candidate [[5], and http://genome.ucsc.edu/].…”
Section: Introductionmentioning
confidence: 99%